2008
DOI: 10.1038/nn2043
|View full text |Cite
|
Sign up to set email alerts
|

A voice region in the monkey brain

Abstract: For vocal animals, recognizing species-specific vocalizations is important for survival and social interactions. In humans, a voice region has been identified that is sensitive to human voices and vocalizations. As this region also strongly responds to speech, it is unclear whether it is tightly associated with linguistic processing and is thus unique to humans. Using functional magnetic resonance imaging of macaque monkeys (Old World primates, Macaca mulatta) we discovered a high-level auditory region that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
227
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(262 citation statements)
references
References 49 publications
28
227
3
Order By: Relevance
“…Furthermore, lesions to the right hemisphere in humans can result in spatial hemi-neglect (Bisiach et al, 1984). In monkeys, previous neuroimaging work has focused on hemispheric biases for vocal sounds (Gil-da-Costa et al, 2006; Ortiz-Rios et al, 2015; Petkov et al, 2008; Poremba et al, 2004); however, until now, no functional MRI study in monkeys utilizing spatial sounds had been performed. In our present study, we found a dynamic BOLD modulation in both hemispheres for spatial (non-vocal) broad-band noise sounds.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lesions to the right hemisphere in humans can result in spatial hemi-neglect (Bisiach et al, 1984). In monkeys, previous neuroimaging work has focused on hemispheric biases for vocal sounds (Gil-da-Costa et al, 2006; Ortiz-Rios et al, 2015; Petkov et al, 2008; Poremba et al, 2004); however, until now, no functional MRI study in monkeys utilizing spatial sounds had been performed. In our present study, we found a dynamic BOLD modulation in both hemispheres for spatial (non-vocal) broad-band noise sounds.…”
Section: Discussionmentioning
confidence: 99%
“…Petkov et al discovered distinct regions of temporal cortex in the brains of Macaque monkeys sensitive to vocalizations and musical instruments [23]. Similarly, Leaver and Rauschecker demonstrated that regions of the human auditory cortex are selective for human speech and musical instrument sounds, suggesting that the other patterns of sensitivity revealed in primate brains may exist in the human auditory cortex as well [24].…”
Section: Central Auditory Nervous System Sites Potentially Damaged Bymentioning
confidence: 97%
“…As shown schematically in the Figure, Schematic representation of organization of central auditory system [15,[21][22][23][24][25][26][27][28][29].…”
Section: Central Auditory Nervous System Sites Potentially Damaged Bymentioning
confidence: 99%
See 1 more Smart Citation
“…A functional imaging study using macaques compared auditory responses to their own species-specific calls with control sounds that had the same spectral profile and duration, other animal vocalizations and natural sounds [19]. Macaques, it seems, do have a voice area that is especially sensitive to conspecific vocalizations in the same manner as the human voice region [20] (though the anatomical location is different; [21]).…”
Section: Vocalization- and Voice-sensitivity In The Neocortexmentioning
confidence: 99%